EDUPRANEURSHIP IN FOSTERING ENTREPRENEURIAL VALUES IN EARLY CHILDHOOD - Zayyana Zahrotul Fitri; Nurhusna Kamil; Nurhusni Kamil; Hellya Rahmatun Nisa; Erni Munastiwi (Universitas Al-Hikmah Indonesia, 2023)
In the field of edupreneurship education is a new innovation that is able to produce human resources of superior quality, creative, independent, competitive, and positively contributes to the development of human resources, quality, creative, independent, competitive, and positively contributes for many individuals. This study endeavors to determine edupreneurship in fostering entrepreneurial values in children through guidance and direction from teachers and parents. The research design employed is study literature review. Literature search through google scholar by collecting books and articles related to the keywords